Influence of hydrogen flow rates annealing on the structural, optical and electrical properties of sol-gel synthesized Fe doped In2O3 films - Noor Baa`yah Ibrahim,; N.F. Zulkifli,; Lau, L.N.; A.Z. Arsad,; N. Yusop, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Diluted magnetic semiconductors (DMSs) have always been of great interest to study due to their wide applications in spintronics. This research was carried out to study the influence of different hydrogen gas flow rates annealing on the physical properties of Fe doped indium oxide. In1.92Fe0.08O3 thin films were prepared by a sol-gel method and followed by a spin coating technique. Different flow rates of hydrogen gas were applied during the annealing process. All samples showed high orientation along the (222) direction and exhibit a polycrystalline structure. Grain size increased as the flow rate increased due to the stronger reduction of H2. FTIR studies showed the existence of an O-H bond in the range of 3000 - 4000 cm-1 and it was caused by the flow of H2 gas during the annealing process. The resistivity of In1.92Fe0.08O3 thin films decreased and the carrier concentration increased with increasing hydrogen flow rates. This work has significance on the size-dependent properties and the chemical bonding in Fe doped In2O3 films.